Interslavic Borrowings-Polonisms in Russian Office Language of the 17th Century - Garbul, Liudmila (Respectus Philologicus, 2005)
The article tackles the problem of the formation of the new Russian literary language in the 17th and 18th centuries and points out some factors that influenced it. They are as follows: the role of office language in that process and the influence of the Polish language, which manifested through the office language at that period. The main emphasis is put on the analysis of the history of such lexemes: okazanje (’evidence, witness, confirmation’), okop (‘trench’), okopatisia (‘open trenches and hide from enemies in them’), pobuditel (a person who encourages somebody to do something), podushchenje (‘the act of encouraging’), postoronnij (‘stranger, foreigner’). The listed lexemes are found in the documents of the ambassador’s order in the 17th century. They prove the intra-Slavic derivatives in the Russian written language of the 16th and 17th centuries to be inter-Slavic lexical borrowings-polonisms.
Keywords: the third southern Slavic influence; ecclesiastical Slavic-Russian diglossia; ecclesiastical Slavic-Russian bilingualism; office language; prostaja mova; Polish-Russian language contacts; intraslavic derivatives; interslavic borrowings; polonisms